Game theoretic sponsored content management in mobile data market - Xiong, Zehui (Nanyang Technological University, 2020)
A sponsored content policy enables a content provider to pay a mobile network operator, and thereby mobile users can access contents from the content provider through network services from the network operator with lower charge. As a result, the content provider and users are both actively engaged into the sponsored content ecosystem. As such, a key challenge is how to provide proper sponsorship in the situation of complex tripartite interactions among the three entities, namely, the network operator, the content provider, and users. In this thesis, we mainly study the game-theoretic interactions among the three entities under the sponsored content policy.